2012
DOI: 10.1155/2012/831201
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Computer Products Sales by Integrating Ensemble Empirical Mode Decomposition and Extreme Learning Machine

Abstract: A hybrid forecasting model that integrates ensemble empirical model decomposition (EEMD), and extreme learning machine (ELM) for computer products sales is proposed. The EEMD is a new piece of signal processing technology. It is based on the local characteristic time scales of a signal and could decompose the complicated signal into intrinsic mode functions (IMFs). The ELM is a novel learning algorithm for single-hidden-layer feedforward networks. In our proposed approach, the initial task is to apply the EEMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…34 First, the CEEMD algorithm, the current extension of the competitive decomposition techniques of EMD and EEMD, is implemented to decompose the original data of crude oil price time series into several relatively independent IMFs and one residue. Second, the EELM tool, a fast and powerful forecasting tool compared with other AI models (e.g., ANN and SVR), is utilized to predict the extracted components independently.…”
Section: Methodology Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…34 First, the CEEMD algorithm, the current extension of the competitive decomposition techniques of EMD and EEMD, is implemented to decompose the original data of crude oil price time series into several relatively independent IMFs and one residue. Second, the EELM tool, a fast and powerful forecasting tool compared with other AI models (e.g., ANN and SVR), is utilized to predict the extracted components independently.…”
Section: Methodology Formulationmentioning
confidence: 99%
“…In existing models, various data decomposition algorithms have been utilized, e.g., EMD, 8 EEMD 33 and wavelet decomposition 35 ; and EEMD has been repeatedly shown to be the most e®ective tool in the EMD family. 33,34 However, there exists a serious drawback in the EEMD algorithm: the large level of residue noise in the signal reconstruction stemming from the added white noises. Even though the residue noise can be mitigated as the ensemble number increases, it would be a time-consuming process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forecasting results were computed exclusively for the following testing sample. We note that in the literature, EMD is instead sometimes applied to the whole dataset, including the testing part (see, e.g., Chen et al 2012;Cheng and Wei 2014;Lin et al 2012;Lu and Shao 2012;Wang et al 2014;Yu et al 2008). The inclusion of (future) testing data in the forecasting methodology is clearly wrong, providing meaningless "forecasts".…”
Section: Datamentioning
confidence: 99%
“…The fundamental concept an integrated forecasting scheme is to capture various patterns in the data by taking advantage of each individual model's capability. The findings have been reported that the two-stage modeling is superior for improving the performance of single-stage modeling [17]- [23]. Since both ARIMA and ANN are appropriate for predicting the IECES, this study considers an integrated ARIMA-ANN as the two-stage model.…”
Section: Introductionmentioning
confidence: 99%